Low zinc serum affects insulin-like growth factor-1 level in dehydrated pregnant women - Mulyani, Erry Yudhya; Hardinsyah, Hardinsyah; Briawan, Dodik; Santoso, Budi Iman; Jus'at, Idrus (International Journal of Public Health Science (IJPHS), 2025)
Maternal body fluids imbalance affects amniotic fluid, serum sodium-potassium, edema, and preeclampsia. Insulin-like growth factor-1 (IGF-1) is a growth hormone and a regulator in sodium balance regulation. This study aimed to determine the correlation of IGF-1, zinc, calcium, and sodium with hydration status and the nutrients impact to IGF-1 based on hydration status of pregnant women at Kebon Jeruk Health-Center, West Jakarta. This cohort-prospective study was conducted in December 2016 to January 2018. A total of 66 pregnant women in the second trimester were examined. Urine color, urine specific gravity, serum sodium, serum osmolality and urine were used as hydration status indicators. Zn, Ca, Na, and IGF-1 levels as the growth indicator from mother to fetus. Pearson correlation test, independent t-test and linear regression were used in statistical analysis. There were no differences in IGF-1, Zn, Ca, and Na serum between the two groups (p³0.05). There was no relationship between Ca, Na and IGF-1 level (p³0.05). The regression results show a possitive relation that low zinc serum affect IGF-1 level in dehydrated pregnant women. Therefore, it is necessary for pregnant women to consume zinc-rich foods to increase IGF-1 level and keep hydration status with water consume 3.0 L per-day.